A new combined system consisting of a molten hydroxide direct carbon fuel cell and an alkali metal thermal electric converter: Energy and exergy analyses. (25th February 2021) - Han, Yuan; Zhang, Houcheng; Hu, Ziyang
Highlights: A new molten hydroxide direct carbon fuel cell-based hybrid system is proposed; Alkali metal thermal electric converter is feasible and effective as bottoming cycle; Hybrid system gains 51.6% increase in maximum power density compared to MHDCFC; Hybrid system's energetic and exergetic efficiencies gain 11.3% and 9.4% increases. Abstract: In addition to electricity, molten hydroxide direct carbon fuel cell also produces a number of high-quality waste heat, which may affect the cell normal operation if the waste heat is not removed immediately. Few efforts have been devoted to recovering the waste heat for additional electricity generation applications yet. In this study, a new combined system model that couples an alkali metal thermal electric converter to a molten hydroxide direct carbon fuel cell is first proposed. Based on the theories of electrochemistry and non-equilibrium thermodynamics, mathematical formulas for the power output, exergy destruction rate, energy efficiency and exergy efficiency of the combined system are deduced. The performance characteristics and optimum criteria of such a combined system are revealed. Numerical calculations show that the maximum output power density of the combined system is improved by 51.6% compared with that of a single molten hydroxide direct carbon fuel cell in the current literature, and its corresponding energy efficiency and exergy efficiency are also increased by 11.3% and 9.4%, respectively. A larger temperature, reactor compartment width, geometric factor for radiation losses or proportional coefficient positively is beneficial for the combined performance improvement, while the thickness of the β ′ ′ -alumina solid electrolyte can be tuned to optimize the combined system performance. The obtained results may offer some guidance for the design and optimization of such an actual combined system.